The Description of Lung Function Status Among Limestone Milling Industry Workers in Tuban Regency - Muhammad Sudrajad; R. Azizah (JURNAL KESEHATAN LINGKUNGAN, 2016)
Abstract: One of air pollution parameters that are harmful to human health is the amount of dust. The main source of the dust pollutant is a limestone grinding activities. The purpose of this study was to look at the description of workers pulmonary function status, physical quality of the work environment, and respiratory complaints that experienced by workers in the limestone milling industry. This research design was descriptive cross sectional study. All of 12 workers in limestone milling industry were recruited in this study. Physical quality of the environment that have seen was the amount of dust particle, air temperature, humidity, and wind speed. Characteristics and respiratory complaints worker measured by questionnaires. Lung function disorder was measured using spirometry. The result of the physical quality measurement of the environment still met quality standards. Respiratory complaints most experienced by workers was phlegm, cough, cough with phlegm, and cold conditions. A total of 100% workers in production and 83.3% of workers in the packing have impaired lung function. It is concluded that, lung function disorders more experienced workers with the working environment had higher levels of dust and higher temperatures, lower humidity. Judging by the characteristics of workers, impaired lung function more experienced workers by aged 20-29 years and 30-39 years old, have years of service more than 5 years, smoking habits, have normal status nutrition, not wearing protective respiratory tract, and not have a history of lung disease. It is suggested that, the workers with impaired lung function should immediately conductfurther tests to get proper treatment. In addition, workers should always wear respirator while working and quiet from smoking behavior.Keywords: dust particle, lung function status, limestone milling industry workers